Data from: Single-cell profiling of muscle-infiltrating T cells in idiopathic inflammatory myopathies - Argyriou, Alexandra; Horuluoglu, Begum; Galindo-Feria, Angeles S.; Diaz Boada, Juan Sebastian; Sijbranda, Merel; Notarnicola, Antonella; Dani, Lara; Van Vollenhoven, Annika; Ramsköld, Daniel; Nennesmo, Inger; Dastmalchi, Maryam; Lundberg, Ingrid E.; et al. (Karolinska Institutet, 2023)
The dataset corresponds to the study by Argyriou, Horuluoglu, Galindo-Feria et. al. Single-cell profiling of muscle-infiltrating T cells in idiopathic inflammatory myopathies. It contains the FASTQ files trimmed by adaptors of RNA-sequencing from single T-cells. There are 3840 cells from muscle biopsies and matched peripheral blood from six donors with idiopathic inflammatory myopathies and one with undefined myopathy.

The cells were sorted using flow cytometry, and RNA-sequencing libraries were generated with the Smartseq2 at the Eukaryotic Single-cell Genomics facility at Science for Life Laboratory in Stockholm, Sweden. Libraries were sequenced on an Illumina Nova seq 6000 (2*100bp) at NGI Stockholm sequencing core facilities, Science for Life Laboratory in Stockholm, Sweden. Additionally, there are smart-seq-3 single-cell transcriptomics from 439 memory T cells from peripheral blood from three healthy donors.

Terms for access

The dataset is only to be used for medical research seeking to advance the fields of immunology, autoimmune diseases, or genetics. After justification and discussion with the study's authors, other research areas could be considered.

To access the dataset, investigators must sign a data transfer agreement with the dataset owners and comply with EU General Data Protection Regulation. The investigators granted access to the dataset must commit to only using it for the research described in their application.  The data set should not be shared with other parties.

For conditional access to the dataset in this publication, please get in touch with datacentre@scilifelab.se
Keywords: Other health sciences not elsewhere classified; Immunology not elsewhere classified; Immunogenetics (incl. genetic immunology); Medical and Health Sciences; Medicin och hälsovetenskap; Immunology; Immunologi; Other Health Sciences; Annan hälsovetenskap